PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATA PELAJARAN IPAS MATERI WUJUD ZAT DAN PERUBAHANYA KELAS IV SDN SIDOMUKTI 03 - Sukma Winahyu, Rachma; M. Yusuf Setia Wardana; Asep Ardiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The main conclusion from this research is that teachers do not utilize media optimally during the science teaching process, causing students to become less responsive and attentive. (1) How to create website-based interactive learning material for science material in the form of substances and its changes in class IV SDN Sidomukti 03, and (2) How to assess interactive website-based learning material for science material in the form of substances and its changes in class IV SDN Sidomukti 3 are the main questions in this research, (3) How are web-based substance and modification learning resources in class IV of SDN Sidomukti received by teachers and students in science class? 3. This research aims to: (1) incorporate website-based interactive learning resources into the science and science curriculum for class IV material at SDN Sidomukti 03; (2) assess the effectiveness of website-based learning resources on Natural Science Materials in the Form of Substances and modifications made to fourth grade students at SDN Sidomukti 03; and (3) understand the reactions of teachers and students to website-based learning resources during the learning of Natural Science material in the Form of Substances and the modifications made to fourth grade students at SDN Sidomukti 03. This kind of research and development uses the ADDIE methodology (Analysis, Design, Development, Implementation, and Evaluation). By using the “very feasible” criteria, practical results were obtained at 97.5%, media results at 93%, student questionnaire results at 95%, and material validation results at 90.5%. The results of the research show that the class IV science and science curriculum at SDN Sidomukti III makes extensive use of website-based learning resources as a learning cool.